Molecular weight of DNA from four entomopoxviruses determined by electron microscopy. - Langridge, W H (1977)
DNA was isolated from entomopoxviruses infected Amsacta moorei and Euxoa auxiliaris (Lepidoptera), Goeldichironomus holoprasinus (Diptera), and Othnonius batesi (Coleoptera) and compared with vertebrate virus DNA (vaccinia). After incubation in Pronase, sodium lauryl sulfate, and deoxycholate, poxvirus preparations shadowed with platinum and palladium revealed subcore particles 45 to 60 nm in diameter. Continued incubation in Pronase resulted in the gradual release of DNA from the particles. Metal-shadowed DNA molecules were photographed in the electron microscope and measured, and the average molecular weights were calculated. Lepidopteran poxvirus DNA (135 X 10(6)) was approximately equal to vaccinia DNA (131.7 X 10(6)) in molecular weight. The molecular weight of dipteran and coleopteran poxvirus DNA (200 X 10(6) to 251 X 10(6)) was approximately 50% greater than vaccinia DNA. Based on the concentration of DNA and protein per virion, Amsacta entomopoxvirus contained 5.7 to 7.7% DNA.